Modeling of Antioxidant Activity, Polyphenols and Macronutrients Content of Bee Pollen Applying Solid-State 13C NMR Spectra - Sylwester Mazurek; Roman Szostak; Mateusz Kondratowicz; Magdalena Węglińska; Agnieszka Kita; Agnieszka Nemś (MDPI AG, 2021)
An application of solid 13C nuclear magnetic resonance (NMR) spectroscopy for the determination of macronutrients, total polyphenols content, antioxidant activity, N C S elements, and pH in commercially available bee pollens is reported herein. Solid-state 13C NMR spectra were recorded for homogenized pollen granules without chemical treatment or dissolution of samples. By combining spectral data with the results of reference analyses, partial least squares models were constructed and validated separately for each of the studied parameters. To characterize and compare the models' quality, the relative standard errors of prediction (RSEP) were calculated for calibration and validation sets. In the case of the analysis of protein, fat and reducing sugars, these errors were in the 1.8-2.5% range. Modeling the elemental composition of bee pollen on the basis of 13C NMR spectra resulted in RSEPcal/RSEPval values of 0.3/0.6% for the sum of NHCS elements, 0.3/0.4% for C, 1.8/1.9% for N, and 4.2/6.1% for S quantification. Analyses of total phenolics and ABTS antioxidant activity resulted in RSEP values in the 2.7-3.5% and 2.8-3.8% ranges, respectively, whereas they were 1.4-2.1% for pH. The obtained results demonstrate the usefulness of 13C solid-state NMR spectroscopy for direct determination of various important physiochemical parameters of bee pollen.